The role of the broader autism phenotype in anxiety and depression in college-aged adults - Kurtz, McKayla R.; Kana, Rajesh K.; Rivera, Daphne L.; Newman, Sharlene D. (Frontiers in Psychiatry, 2023)
The current study examines the relationship between the presence of autistic traits and anxiety and mood disorders in young adults from different racial groups. A representative sample from a predominately white university (2,791 non-Hispanic White (NHW) and 185 Black students) completed the broad autism phenotype questionnaire (BAPQ), a measure of depression (Patient Health Questionnaire, PHQ-9), and anxiety (Generalized Anxiety Disorder, GAD-7). Statistical Package for Social Sciences (SPSS) was used to perform two factorial ANOVAs to determine the effect of race and BAPQ score on anxiety and depression scores. The current study found that Black participants with autistic traits had higher depression and anxiety scores than did NHW participants. These findings underscore the association between autistic traits and anxiety and depression in Black communities, and the need for further studies on this topic area. Additionally, it highlights the importance of improving access to mental health care for this population.